The Shock of the News : Media Coverage and the Making of 9/11. - Monahan, Brian A. (NYU Press, 2010)
How did the events of September 11, 2001 come to be thought of as 9/11? The Shock of the News is an authoritative account of post-9/11 political and social processes, offering an in-depth analysis of the media coverage of this momentous event. Brian Monahan demonstrates how 9/11 has been transformed into a morality tale centered on patriotism, victimization, and heroes. Introducing the idea of "public drama" as a way of making sense of how media processed and packaged the 9/11 attacks for their audiences, Monahan not only illuminates how and why the coverage took shape as it did, but also prov